Utilization of Sagip Pangarap Intervention Program (SPIP) as a Flexible Learning Strategy for Students-at-Risk of Dropping-Out - Gecolea, Peejay (JPAIR Institutional Research, 2019)
Sagip Pangarap Intervention Program (SPIP) is intended for students at risk of dropping out. The validated handbook provides a clear view and guides for the users as to how this program will be implemented and monitored. It aimed to determine the effectiveness of the SPIP manual in the attendance and class participation of the students at risk of dropping out; a mixed-method research design was utilized. The participants were the 15 Grade 8 students of Calamba Bayside Integrated School enrolled during the SY 2018-2019; these students were considered SARDOs after thorough monitoring and evaluation of advisers and grade-level key teachers. The participants were chosen through purposive sampling. Results showed that there is a decrease (89. 88%) in the number of absences incurred by the SARDOs after the implementation of the intervention program. It also revealed that in terms of class participation, the results of the interview conducted to the selected teachers and parents implied that the program helped the students to regularly come to school and improve their class participation since it provides different options, strategies, approaches, and opportunities for the students regarding their schooling. Since the use of this intervention program is proven effective, it is recommended that SPIP be used by teachers to help students in improving their performance in terms of attendance and class participation.